Evaluation of a four-component composite landfill liner system. Issue 4 (11th March 2015) - Stark, Timothy D.
Abstract : The performance of four different municipal solid waste landfill liner systems common in the United States, that is, USEPA Subtitle D prescribed composite liner system, composite liner system consisting of a geomembrane (GM) overlying a geosynthetic clay liner (GCL), Wisconsin NR500 liner system, and a proposed four-component composite liner system that is a combination of the GCL composite liner and Subtitle D liner system (with a 61-cm or 91·5-cm thick low hydraulic conductivity compacted soil), were evaluated in terms of leakage rate, solute mass flux, and cumulative solute mass transport. Leakage rates through circular and non-circular GM defects were analysed using both analytical and numerical methods. For the mass flux evaluation, solute transport analyses using GM defects and diffusion of volatile organic compounds through intact liners were conducted using one- and three-dimensional numerical models. Cadmium and toluene were used as typical inorganic and organic substances, respectively, in the analyses. The comparison shows that for the limited set of conditions considered, the four-component composite liner system outperforms the Subtitle D and Wisconsin NR500 liner systems based on leakage rate and mass flux and provides similar results to the GM/GCL liner system. Based on the analyses presented herein the four-component liner system is a viable choice for a protective Subtitle D composite liner system and provides some added protection to the GCL.